The sustainability of Ar-Rahnu practices - Juliza binti Mohamed, Azlan Ali, Rashidah Kamarulzaman, Zainal Azhar bin Zainal Azim,; Hafezali Iqbal Hussain, Amirul Syafiq bin Ghazali, Aza Azlina binti Md Kassim, (Opción, 2019)
This research examines the factors (brand image, brand loyalty and perceived value) contribute to the brand equity of Ar-Rahnu Pawnshop. 150 questioners have been distributed in Klang Valley area and only 100 questionnaires were returned. Five Likert scale questionnaire were employed. Linear regression method has been used to diagnose the relationship between each independent and dependent variable. As a result, brand image and brand loyalty show significant relationship to dependent variables. In conclusion, the managerial implication would be that image and loyalty are critical areas in building a sustainable Ar-Rahnu practice.